Fermentation Profiles, Bacterial Community Compositions, and Their Predicted Functional Characteristics of Grass Silage in Response to Epiphytic Microbiota on Legume Forages - Wang, Siran; Shao, Tao; Li, Junfeng; Zhao, Jie; Dong, Zhihao (Frontiers in Microbiology, 2022)
This study aimed to investigate the effect of epiphytic microbiota from alfalfa and red clover on the fermentative products, bacterial community compositions and their predicted functional characteristics in Italian ryegrass silage. By microbiota transplantation and γ-ray irradiation sterilization, the irradiated Italian ryegrass was treated as following: (1) sterile distilled water (STIR); (2) epiphytic microbiota on Italian ryegrass (IRIR); (3) epiphytic microbiota on alfalfa (IRAL); (4) epiphytic microbiota on red clover (IRRC). The irradiated Italian ryegrass was ensiled for 1, 3, 7, 15, 30, and 60 days, respectively. STIR had similar chemical components with fresh Italian ryegrass. IRAL had higher lactic acid concentrations (64.0 g/kg dry matter (DM)) than IRIR (22.3 g/kg DM) and IRRC (49.4 g/kg DM) on day 3. IRRC had the lowest lactic acid concentrations (59.7 g/kg DM), and highest pH (4.64), acetic acid (60.4 g/kg DM), ethanol (20.4 g/kg DM) and ammonia nitrogen (82.6 g/kg DM) concentrations and Enterobacteriaceae (9.51 log10 cfu/g fresh weight (FW)) populations among treatments on day 60. On day 3 and 60, Lactobacillus was both dominant in IRIR (42.2%; 72.7%) and IRAL (29.7%; 91.6%), while Hafnia-Obesumbacterium was predominant in IRRC (85.2%; 48.9%). IRIR and IRAL had lower abundances of ‘Membrane transport’ than IRRC on day 3. IRIR and IRAL had lower abundances of phosphotransacetylase and putative ATP-binding cassette transporter, and higher abundances of arginine deiminase on day 3. IRAL had the highest abundance of fructokinase on day 3. Overall, inoculating epiphytic microbiota from different legume forages changed the fermentative products, bacterial community compositions and their predicted functional characteristics in Italian ryegrass silage. The microbial factors that result in the differences in fermentative profiles between legume forage and grass were revealed. Knowledge regarding the effect of epiphytic microbiota could provide more insights into the improvement of silage quality.